2021
DOI: 10.21608/jdea.2021.53384.1004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Statues, Growth and Some Physiological Performances of the Gimmizah Male Chickens Supplemented by Dietary Spirulina Platensis under Chronic Heat Stress.

Abstract: The present study was carried out to study the effect of Spirulina supplementation on the growth and some physiological performances of the Gimmizah males exposed to heat stress (HS). A total number of 150 male 4 weeks old Gimmizah were randomly allocated in five groups (3 replicates, 10 chicks each). The first (positive control, PC) was reared under 22-24OC and PH 45-55% and fed unsupplied basal diet, B). Whereas, the other groups were reused under HS (38°C±1; 55-65 % RH) for three successive days /wk from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…AST and ALT concentration significant decrease for the Spirulina groups (Table 7.) this results in agreement with Abaza et al (2021) and Jamil et al (2015) who reported that ALT and AST activity significantly decreased in all treatment groups supplemented with spirulina , therefore Zeweil et al (2019) results indicated that different supplementations as Spirulina 0.5 and 1 g\kg diet decreased adverse effect of heat stress on ALT and AST of chickens, and there was a slight decrease in plasma ALP and liver enzymes activities the obtained values are fell within the normal range groups in the present study and may reflect normal liver function. The decrease in ALP, ALT and AST actives were observed among supplemented groups.…”
Section: Liver Function Testssupporting
confidence: 92%
See 2 more Smart Citations
“…AST and ALT concentration significant decrease for the Spirulina groups (Table 7.) this results in agreement with Abaza et al (2021) and Jamil et al (2015) who reported that ALT and AST activity significantly decreased in all treatment groups supplemented with spirulina , therefore Zeweil et al (2019) results indicated that different supplementations as Spirulina 0.5 and 1 g\kg diet decreased adverse effect of heat stress on ALT and AST of chickens, and there was a slight decrease in plasma ALP and liver enzymes activities the obtained values are fell within the normal range groups in the present study and may reflect normal liver function. The decrease in ALP, ALT and AST actives were observed among supplemented groups.…”
Section: Liver Function Testssupporting
confidence: 92%
“…On the other hand, Abaza et al (2021) found that the final body weight was not significant differed among different experimental groups at the end of experiment. Algae implies the presence of more than one group of growth-prompting substances such as (auxins, cytokinins and gibberellins) which may be influenced the body growth (Michalak et al, 2016).…”
Section: Productive Performance and Carcass Traitsmentioning
confidence: 79%
See 1 more Smart Citation